Biology of Euphorbia prunifolia jacq. seeds - Chin, Hoong Fong; M. Ali, Sabudin (Organising committee of Eighth Asian-Pacific Weed Science Society Conference, 1981)
Euphorbia prunifolia Jacq. has a very short life cycle of 3 months and each plant is capable of producing an average of 720 seeds. An estimated 720.7 million seeds can be produced from a hectare in a season. From soil samples, 30 million seeds are found in the top 10 cm of soil. Seeds remain viable and dormant for a long period buried in soil, they germinate readily once brought to soil surface. Mature as well as immature seeds from green pods germinate readily with 90 -100% germination. Dry and moist heat treatment at above 50° C for 48 hr reduce their germination and killed seeds at 60° C. Moist heat is more effective, at 45° C there is a significant drop in percentage germination. Polythene sheets placed on top of soil raised soil temperature from 40° C to 66° C at noon and prevented the germination of these seeds. Thus polythene sheets can be used especially in undisturbed soil of minimal tillage to control Euphorbia prunifolia in annual crops..